HUBUNGAN PENGGUNAAN TABIR SURYA DENGAN KEJADIAN MELASMA PADA PEGAWAI WANITA DI DINAS PERHUBUNGAN KOTA SEMARANG - Adhi Pramudya, Dimas Sigit; Krisnarto, Eko; Setiawan, M Riza (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Melasma is hyperpigmentation disorder in form of dark brown irregular macules which thought to caused excessive sun exposure. Regular and correct use of sunscreen is recommended as prevention from UVA and UVB rays, especially for people who have high risk of long-term sun exposure. The purpose of this study was determine the relationship between history of using sunscreen and the incidence of melasma and differences between respondents who used sunscreen compared to respondents who did not use sunscreen on the incidence of melasma. This research is observational analytic study with cross-sectional quantitative approach to female employees at the Semarang City Transportation Office. Obtained 45 samples through total sampling method. Data collection obtained from the anamnesis and respondents' answers through personal data sheets, questionnaires that been distributed and the results of physical examination using wood lamp as well as results of taking photos on the respondent's face which been consulted with dermatologist and genital specialist who met the inclusion and exclusion criteria which then analyzed with SPSS. The results showed that there was significant relationship between history of using sunscreen and incidence of melasma (P<0.05) and there was significant relationship between duration of sun exposure and incidence of melasma (P<0.05). There is significant relationship between history of using sunscreen and incidence of melasma and there is significant difference between respondents who have history of using sunscreen and those who do not have history of using sunscreen with incidence of melasma.